Graduate Researchers & Students: HESI SDG Publishers Compact Fellows Top Action Tips (ScienceOpen Research)
Recommendations for students and graduates on how to build SDGs into new and ongoing projects. Graduate students are preparing to enter an academic and career climate that is burdened with two tasks: addressing the mistakes of the past and forging a habitable future for all. The United Nations Publishers Compact SDG Fellows are confident that these tips will introduce a pathway towards participation in the Sustainable Development Goals (SDGs). To ensure those choosing the challenge of achieving the SDGs by 2030, our recommendations are for masters, doctoral and postdoctoral students, who can move the needle by leveraging their personal and institutional power.